Critical Discourse Analysis: Representation of Religious Ideology and Social Morality in The Novel Dalam Mihrob Cinta by Habiburrahman El Shirazy - Helmi Wicaksono; Ary Fawzi; Anang Santoso; Mochammad Syahri (Aksara, 2025)
This study aimed to reveal the representation of religious ideology and social morality in the novel Dalam Mihrab Cintaby Habiburrahman El Shirazy using the Critical Discourse Analysis (CDA) approach of the Norman Fairclough model. This study used a descriptive qualitative method with a three-dimensional analysis framework: textual (linguistic), discourse practice (interpretation), and social practice (explanation). The findings revealed that the novel constructed a religious value hegemony through symbols, language patterns, and narrative structures emphasizing repentance, honesty, responsibility, and the roles of women and communities in character formation. Additionally, the Islamic boarding school setting and the author’s identity as a da’i further reinforced the religious ideology embedded in the text. The study also found that the novel offered a critique of social inequality framed through religious morality, positioning literature as an effective medium for disseminating conservative values in modern society. These findings carried implications for character education, religious literature curricula, and the development of discourse-based critical literacy. AbstrakPenelitian ini bertujuan untuk mengungkap representasi ideologi religius dan moralitas sosial Novel Dalam Mihrab Cinta karya Habiburrahman El Shirazy dengan menggunakan pendekatan Analisis Wacana Kritis (AWK) model Norman Fairclough. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik analisis tiga dimensi, yaitu teks (linguistik), praktik wacana (interpretasi), serta praktik sosial (eksplanasi). Hasil analisis menunjukkan bahwa novel secara eksplisit membangun hegemoni nilai religius melalui simbol, struktur bahasa, dan konstruksi narasi yang menekankan pada tobat, kejujuran, tanggung jawab, serta peran perempuan, dan komunitas dalam pembentukan karakter. Selain itu, latar pesantren dan identitas pengarang sebagai da’i turut memperkuat ideologi religius yang diinternalisasi dalam teks. Penelitian ini juga menemukan bahwa novel ini mengkritik ketimpangan sosial dengan bingkai keadilan melalui moralitas religius, serta menjadikan sastra sebagai medium penyebaran nilai-nilai konservatif yang efektif dalam masyarakat modern. Temuan ini berimplikasi pada pengembangan pendidikan karakter, kurikulum sastra religius, dan literasi kritis berbasis wacana.